EDUKASI TENTANG OBAT HERBAL (UNTUK DEMAM) BERDASAR FORMULARIUM RAMUAN OBAT TRADISIONAL INDONESIA (FROTI) - Siswi Wulandari; Agung Nugroho Widhi; Nadya Sukma Larasati; Juliana Putri Handayani (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2022)
Indonesian people have been using traditional Indonesian medicinal ingredients for health care, disease prevention, and health care since ancient times. Health education is very necessary considering that the ingredients in FROTI are used as a complement to treatment if used in conjunction with conventional medicine after being communicated to medical personnel (doctors). Community service is carried out by providing training on the rational use of ingredients and according to the instructions for use, it is hoped that it can help the community in maintaining and improving health for 100 respondents (community) and will be held in July 2022 in the Campurejo village, Kediri City. The method used is counseling while still paying attention to health protocols. Activities in community service with SAP Health education in order to increase knowledge about updating the use of herbal medicines by utilizing Family Medicinal Plants in the surrounding area. Community service by providing health education 15 respondents had good knowledge before counseling and 75 respondents had good knowledge after health education. Community service by providing the practice of making herbal medicines 15 respondents had a good category before counseling and 35 respondents had a good category after the practice of making herbal medicines.